Edukasi Pertolongan Pertama Pada Kecelakaan (P3K) Bagi Siswa Sekolah Menengah - Noor, Mohammad Arifin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Accidents can happen anytime and anywhere, including in the school environment. Knowledge and skills regarding First Aid (P3K) are crucial for high school students to provide appropriate initial assistance before medical personnel arrive. This community service activity aims to improve students' knowledge and skills in providing first aid in emergencies at school. The activity's implementation methods included interactive lectures, discussions, and hands-on practice of first aid treatment for various cases such as wounds, broken bones, fainting, and bleeding. The activity was conducted at a high school in City X with 50 participants. Evaluation results showed an 85% increase in student knowledge compared to before the training. Furthermore, students demonstrated improved practical skills in administering first aid appropriately and safely. In conclusion, first aid education is highly effective in improving students' preparedness for accidents in the school environment.